INOVASI PRODUK SISTIK JAMBAL ROTI MENTEGA SEBAGAI OLEH-OLEH KHAS PANGANDARAN - Astiana, Rachmat; Fadilah, Lita (JURNAL GASTRONOMI INDONESIA, 2024)
This research cover show the formulation process of making Sistik innovations from salted fish ingredients jambal roti typical of Pangandaran Beach. And to find out how the results of this experiment are based on color, aroma, taste, and texture. Thus, this study aims to determine the formulation based on consumer acceptability to processed products of salted fish steak innovation jambal roti. The method used in this study is an organoleptic test. According to the limited panelists of five people and the consumer panelists of thirty people, each panelist has different conclusions from the aspects of color, aroma, taste and texture. Which results were obtained from this study that, this innovative product of salted fish jambal roti can be well received by the panelists. So that later this product can be traded into a typical UMKM product of Pangandaran.